PEMBATALAN HAK MEREK DAGANG TERDAFTAR BERDASARKAN UU NO. 20 TAHUN 2016 (STUDI PUTUSAN NO. 535 K/PDT.SUS-HKI/2018) - Calvin Stanley; Antonius Jingga; Cyntia Fadhillah; Suhaila Zulkifli (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2020)
Brand is a part of intellectual work that has a role to add and improve business both in the form of goods or in the trade and investment sector that needs to be supported. In Indonesia regulation about trademark regulated in UU No. 20 Tahun 2016 tentang Merek dan Indikasi Geografis. In this research, the authors discuss about the procedure for brand registration, as well as its requirements like formality checks, and substance that must be completed and after the examination completed, then continued in certification and announce on the brand. And as a result of the cancellation of a trademark that has rights in principle or whole with a trademark owned by another party conducted by PT PUSAKA IWAN TIRTA against PT IWAN TIRTA (Study of Decision No.535 K / Pdt.Sus-Hki / 2018). The research method used is Normative Juridical. The legal sources used are primary, secondary, and tertiary. The data collection method is by during a literature study. Data analysis is obtained qualitatively. In brand registration, there are several procedures such as formality checks, substantive checks, announcements, and certifications. There are 2 types of punishing set in the UU Merek dan Indikasi Geografis, namely civil and criminal penalties